MARSEILLE - Vacher, Mark (Tidsskriftet Antropologi, 2003)
Even to people who have never sat foot in Marseille, it is known to be a corrupt and dangerous place. In this article I examine the relation between reputation, experience and the city. How did Marseille’s bad reputation come into being, and what consequences does it have for the way the city is experienced by first time visitors?